Comparative Analysis of Nuclear Power Plant and Thermal Power Plants Using Analytic Hierarchy Process (AHP) - Yanuar Zulardiansyah, Arief; Erdawaty, Samsul; Mohd Hafiez Izzwan, Saad; Hamzah, Eteruddin (2020)
In Malaysia, fossil fuels are the most frequently used as energy resource. However, the amount of reserves for fossil fuels is now declining. That is why nuclear energy has become more popular for a certain country to diversify its production of energy. The aim of this paper is to analyze the suitability of nuclear power plant (NPP) compared to conventional power plants using a multi-criteria decision-making technique or known as the Analytic Hierarchy Process (AHP). A framework of AHP’s hierarchy is being developed, and the hierarchy structure consists of six criteria, namely safety and security, resources, public acceptance, cost of energy, construction time, and CO2 emission, respectively. Other than that, three alternatives, namely NPP, thermal power plant and hydropower plant, are also considered in the hierarchy structure. By using AHP technique, the system reveals that the hydropower plant is the most favourable choice of a better power plant compared with others. The results obtained demonstrate the validity of the framework developed.